Proizvodnja in raba lesne biomase v Sloveniji - Krajnc, Nike (Gozdarski vestnik, 2009)
The article deals with the state of the art of wood biomass production and usein Slovenia. Production of wood fuel, wood chips and wood pellets are estimated. Current use of wood biomass is estimated for households, industry and energy sector.
Keywords: lesna biomasa; sekanci; raba energije; Slovenia; Slovenija